Outside air design parameters and climate regions for calculating building space cooling loads in Poland - Narowski, Piotr (Instal, 2020)
Design space cooling loads of building ventilation and air conditioning systems depend on many parameters of the external and internal space of buildings and their variability in a representative period taken for calculations. The value of space cooling loads for a building depends to the greatest extent on the total intensity of solar radiation and the parameters of the outside air. Calculation parameters of the outdoor air for cooling, ventilation and air conditioning must take into account the possibility of calculating the design cooling capacity of sensible heat and latent heat associated with drying the ventilation air. Therefore, the calculation parameters of the outside air should enable the determination of both its dry bulb temperature and the moisture content and enthalpy of the humid air. It is customary to calculate the cooling, ventilation and air-conditioning systems by designers using the climatic zones and the parameters of the outside air assigned to them, given in the withdrawn standard PN-B 03420: 1976 [1], compiled on the basis of meteorological data from the 1960s and 1970s. The article presents the values of the design parameters of the outside air for the Polish climatic zones determined on the basis of measurement data from 58 Polish meteorological stations and 68 meteorological stations located in the neighboring countries in the area of Central Europe. The values of the design parameters of the outside are presented on the maps of Poland divided into Voronoi areas and by means of climatic zones separated by isolines and in tabular form.